IMPLEMENTASI MANAJEMEN KURIKULUM MERDEKA MELALUI SISTEM BLOK DALAM PENINGKATAN EFEKTIFITAS PEMBELAJARAN BERBASIS PROJEK DI SMK NEGERI 1 SANGATTA UTARA - Paridah; Haeruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe how the implementation of the independent curriculum management through the block system at SMK Negeri 1 Sangatta Utara, to find out whether through the Block system learning can increase the effectiveness of project-based learning at SMK N 1 Sangatta Utara. The research method is qualitative and the research subjects are 40 people at SMK Negeri 1 Sangatta Utara. Data collection was carried out through observation, interviews, and documentation. Qualitative data analysis techniques use interactive data analysis consisting of data collection, data reduction, data presentation, and conclusions. The results of the study indicate that the implementation of the independent curriculum through the block system at SMK Negeri 1 Sangatat Utara was implemented using project-based learning. The implementation of the block system has positive impacts such as teachers having more freedom to prepare materials and learning strategies and assessments, honing students' abilities in cooperation, leadership, time management, critical thinking, creativity, and innovation. However, the implementation of the block system has a negative impact, namely the lack of detail in the delivery of material from several subjects. Based on the results of data processing through interviews with sources and respondents, the implementation of the block system at SMK Negeri 1 Sangatta Utara is effective seen from the aspects of clarity of information, preparation, and implementation of the block system. Thus, the implementation of the independent curriculum management through a block system in project-based learning at SMK Negeri 1 Sangatta Utara was more effective because it had a positive impact on learning for both teachers and students.